Occurrence Rate and Outcomes of Weaning Groups According to a Refined Weaning Classification: A Retrospective Observational Study*. Issue 5 (8th February 2023) - Van Hollebeke, Marine; Ribeiro Campos, Débora; Muller, Jan; Gosselink, Rik; Langer, Daniel; Hermans, Greet
Abstract : OBJECTIVES: The weaning according to a new definition (WIND) classification groups mechanically ventilated (MV) patients into "short weaning, " "difficult weaning, " "prolonged weaning, " and "no weaning." The aims of the study were: 1) to describe the weaning group distribution, 2) to evaluate if "short weaning" patients can be divided into groups with distinct characteristics and outcomes depending on the MV duration, and 3) to study 1-year outcomes related to weaning groups. DESIGN: Retrospective observational study. SETTING: Tertiary center with a mixed, mainly surgical ICU population. PATIENTS: MV patients admitted between April 11, 2018, and April 10, 2019. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: A refined WIND classification was used, dividing "short weaning" patients into patients MV less than or equal to 24 hours, "short weaning a, " and those MV greater than 24 hours, "short weaning b." Data were collected from electronic medical records. Of 1, 801 MV patients, 65% were categorized as "short weaning a, " 13% "short weaning b, " 8% "difficult weaning, " 6% "prolonged weaning, " and 8% "no weaning." "Short weaning a" patients were older, more frequently male, and had lower disease severity compared with "short weaning b." Weaning duration (days: 0 [0–0] to 14 [10–21]), weaning success rate (99–69%), ICU length of stay (days: 2 [1–4] to 28 [19–48]), ICU mortality (1–37%), and hospital length of stay (days: 10 [7–18] to 48 [27–89]) and hospital mortality (4–42%; all p < 0.01) increasingly worsened from "short weaning a" to "prolonged weaning." One-year mortality increased from "short weaning a" (9%) to "short weaning b" (27%), "difficult weaning" (39%), and "prolonged weaning" (49%). In adjusted analyses, weaning groups remained independently associated with 1-year mortality. CONCLUSIONS: The high proportion of "short weaning" patients in this mainly surgical ICU population could be divided into two groups with distinct characteristics. This refined WIND classification allowed to enhance prognostication, also beyond hospitalization, highlighting the need to further optimize the weaning process.